Upgrading sequencing batch reactor using attached biofilm. (1st April 2021) - Abdelaziz, Hossam A.; Fouad, Moharram; Mossad, Mohamed
Abstract: A conventional sequencing batch reactor (SBR) was upgraded using fixed biofilm carriers with a specific surface area around 18 m 2 m −3 . The upgraded SBR was investigated to remove phenol from high strength wastewater operated under various operational conditions. The operational conditions used were variable volume exchange ratio (VER) up to 75%, hydraulic retention time (HRT) from (10.7–21.3 hr), aeration time (from 2 to 8 hr), and initial phenol concentration up to 600 mg L −1 . It was found that the upgraded SBR increased the removal efficiencies of biological oxygen demand (BOD5 ), chemical oxygen demand (COD), and total suspended solids (TSS) by about 10% using high strength wastewater without phenol compared to SBR. Furthermore, the removal rate of phenol for the upgraded SBR was higher than conventional SBR by about 18% at 600 mg L − of initial phenol concentration under the same operational conditions. Compared to the conventional SBR, the upgraded version reduced the aeration step by 25% and achieved higher removal efficiency of phenol. Moreover, it reduced the excess sludge by about 23% and enhanced its properties by lowering the sludge volume index (SVI) by about 33%. Practitioner points: Upgrading conventional SBR by adding biofilm carriers is necessary for wastewater treatment with high strength wastewater. The upgraded SBR has a higher resistance toward phenol compound due to the presence of the attached biofilm. The upgraded SBR enhances sludge settling properties, decreases the amount of excess sludge, and also reduces the start‐up period. The number of cycles per day by upgraded SBR was more than the conventional SBR by 15%. The upgraded SBR is an effective system and has good operational stability. Abstract : The conventional sequencing batch reactor (SBR) was upgraded by adding fixed fiberglass biofilm carriers. The upgraded SBR improved removal efficiencies by 10% under a high volume exchange ratio equal to 75%, increased the treated volume of wastewater by 15%, and gave a higher phenol removal rate by 16% compared with the conventional SBR. It can be considered an effective system for municipal and industrial wastewater.